Cindy Sherman or about some Cinema and Television Stereotypes - Annateresa Fabris (Revista Estudos Feministas, 2003)
In Untitled Film Stills and Rear Screen Projections Cindy Sherman performs critically the stereotypes that rule the image of the woman as a product of the masculine gaze.